1996
DOI: 10.2134/jpa1996.0418
|View full text |Cite
|
Sign up to set email alerts
|

Plant Persistence and Animal Performance for Continuously Stocked Alfalfa Pastures at Three Forage Allowances

Abstract: Alfalfa (Medicago sativa L.) has not been well suited for pasture because of its intolerance to grazing. ‘Alfagraze’, a cultivar bred for grazing tolerance, offers potential to use alfalfa as pasture. A 3‐yr grazing study was initiated in central Georgia to investigate persistence and animal performance of ‘Apollo’ and Alfagraze alfalfa at low, medium, and high forage allowance (FA). The FA for this study were targeted at 1000, 2000, and 3000 lb dry matter (DM)/1100 lb animal unit for low, medium, and high FA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
2

Year Published

2000
2000
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 13 publications
2
28
0
2
Order By: Relevance
“…Animal performance trials at the University of Georgia showed that maintaining alfalfa stand density provided higher animal gains under continuous grazing at high stocking rates (Table 4) Bates et al 1996). These data are extremely important because they show that a grazing-tolerant cultivar can result in more saleable animal product for the producer.…”
Section: Animal Performancementioning
confidence: 99%
“…Animal performance trials at the University of Georgia showed that maintaining alfalfa stand density provided higher animal gains under continuous grazing at high stocking rates (Table 4) Bates et al 1996). These data are extremely important because they show that a grazing-tolerant cultivar can result in more saleable animal product for the producer.…”
Section: Animal Performancementioning
confidence: 99%
“…Butler et al (2012) evaluated four alfalfa varieties under stocking and reported that excessive stand loss (>50%) of alfalfa occurred between the end of the third year and beginning of the fourth year for both grazing systems. Cultivars such as Alfagraze that were selected for grazing tolerance have increased the use of alfalfa due to its nutritive value, persistence under continuous stocking, and potential profits (Smith et al, 1989;Smith and Bouton, 1993;Bates et al, 1996;Bouton et al, 1998;Bouton and Gates, 2003). Grazing could potentially shift the mixture toward bermudagrass because of its sod forming nature, deep rooting abilities, and the susceptibility of alfalfa to frequent defoliation.…”
mentioning
confidence: 99%
“…Developing proper defoliation management is critical in gaining acceptance and use of alfalfa as a grazing resource (Bates et al 1996). Medicago falcata alfalfa may have different responses to grass competition and defoliation management than M. sativa.…”
mentioning
confidence: 99%
“…For instance, alfalfa survival was lower in treatments with a single yearly defoliation of alfalfa in Conservation Reserve Program than in treatments that had three to four cuttings per year (Sheaffer et al 1997). A lower frequency of defoliation in mixed alfalfa-grass stands improved yield (Bittman et al 1991;Hoveland et al 1996) and decreased grass encroachment (Comstock and Law 1948;Bates et al 1996;Hoveland et al 1996).…”
mentioning
confidence: 99%